2021
DOI: 10.1007/s00592-021-01819-2
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine pancreas function is impaired in adult relatives of patients with type 1 diabetes

Abstract: Aims Alterations of the exocrine pancreas have been reported in type 1 diabetes, but their contribution to the pathogenesis of the disease is poorly understood. Here, we investigated markers of exocrine pancreas dysfunction in individuals at-risk of developing type 1 diabetes. Methods Serum P-amylase and lipase levels were assessed in samples obtained from healthy controls, patients with new onset type 1 diabetes, relatives participating to the TrialNet Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a study of 85 children participating in the ENDIA study, levels of Fecal Elastase-1, another marker of pancreatic function, were shown to decrease over time in 28 progressors compared to non-progressors ( 60 ). A study of TrialNet participants at diagnosis and in those with islet autoantibodies showed that lower levels of circulating P-amylase and lipase (both exocrine enzymes) can be detected before the onset of clinical symptoms in at-risk adult individuals, but not in children ( 61 ). Further evidence for the importance of pancreatic enzymes comes from a recent Mendelian Randomisation study to identify circulating proteins influencing type 1 diabetes susceptibility, which showed that increased levels of serum chymotrypsinogen was associated with a decreased risk of T1D ( 62 ).…”
Section: Monitoring Efficacy In Clinical Trialsmentioning
confidence: 99%
“…In a study of 85 children participating in the ENDIA study, levels of Fecal Elastase-1, another marker of pancreatic function, were shown to decrease over time in 28 progressors compared to non-progressors ( 60 ). A study of TrialNet participants at diagnosis and in those with islet autoantibodies showed that lower levels of circulating P-amylase and lipase (both exocrine enzymes) can be detected before the onset of clinical symptoms in at-risk adult individuals, but not in children ( 61 ). Further evidence for the importance of pancreatic enzymes comes from a recent Mendelian Randomisation study to identify circulating proteins influencing type 1 diabetes susceptibility, which showed that increased levels of serum chymotrypsinogen was associated with a decreased risk of T1D ( 62 ).…”
Section: Monitoring Efficacy In Clinical Trialsmentioning
confidence: 99%
“…However, heterogeneity in T1D onset as well as response to therapies calls for a better understanding of pathophysiology and additional markers of risk. Exocrine atrophy precedes the onset of detectable islet autoimmunity in some subjects [ 5 , 6 , 18 , 30 ], signifying that measures of exocrine pancreas size and function could be beneficial early biomarkers. If exocrine loss occurs before the onset of islet autoantibodies, markers of exocrine pancreas size or function could be useful to predict early T1D risk.…”
Section: Using Exocrine Biomarkers In Disease Prediction and Monitoringmentioning
confidence: 99%
“…It has been postulated that patients with T1D exhibit exocrine pancreas dysfunction secondary to a lack of insulin and dysregulation of endocrine function. 13,14 Imaging studies have reported a correlation of the T1 signal intensity ratio (SIR) specifically with pancreatic exocrine dysfunction measured by the endoscopic pancreatic function tests. 15,16 Noda et al 17 reported that pancreatic T1 relaxation time is significantly increased with pre-DM individuals and moderately correlates with HbA1c (glycated hemoglobin), suggesting that T1 has the potential of being an imaging biomarker for DM.…”
Section: Background and Rationalementioning
confidence: 99%
“…We will measure the pancreatic fat signal using MRI, and we expect the fat fraction to be higher in the new-onset DM group compared with the control group. It has been postulated that patients with T1D exhibit exocrine pancreas dysfunction secondary to a lack of insulin and dysregulation of endocrine function 13,14 . Imaging studies have reported a correlation of the T1 signal intensity ratio (SIR) specifically with pancreatic exocrine dysfunction measured by the endoscopic pancreatic function tests 15,16 .…”
Section: Background and Rationalementioning
confidence: 99%